Pengembangan Media Pembelajaran Berbasis Video Pada Pokok Bahasan Elemen Keselamatan dan Kesehatan Kerja Lingkungan Hidup (K3LH) Budaya Kerja Industri Kelas X TKJT di SMK N 5 Padang - Exfrizaldi, Exfrizaldi; Afirian, Adlia; Ade, Regina (Universitas Labuhanbatu, 2024)
The aim of this research is to produce valid and practical video-based learning media on the basic language elements of safety and health at work environment 9k3lh) industrial work culture class X TKJT at SMKN 5 Padang. The method for this learning media uses research and development methods, where the product for developing video-based learning media uses quantitative analysis. The development of this video-based learning media uses ADDIE development which consists of 5 stages: analysis, design, development, implementation and evaluation stages. The results of the media validity test by media expert validators with the usage aspect with an average of 0.708 and the appearance aspect with an average of 0.733 were declared valid for use. The results of the practicality test of learning media carried out at SMKN 5 Padang which was carried out by 1 teacher, several aspects were assessed by the teacher, namely Appearance Aspects 86.66 in the very practical category, Usage Aspects with an average of 83.33 in the very practical category and Aspects Material with an average of 80.95 in the very practical category. Based on data analysis, it can be concluded that learning videos on the subject of occupational safety and health elements, environmental (K3LH) industrial work culture are suitable for use in the learning process.